Utilizing A New Technology of English Discoveries Platform in Implementation of Blended Learning to Improve English Speaking Performance - Waode Hamsia; Yatim Riyanto; Fajar Arianto (Universitas Pendidikan Mandalika, 2020)
This research focused on the implementation of blended learning through the platform of English Discoveries to analyze the relationship between blended learning to take an effort to improve self-regulated learning and learning outcomes in speaking skill. This research used a qualitative approach. The subjects were 20 students of the second semester in speaking class at Muhammadiyah University of Surabaya. The result showed that the implementation of blended learning model can improve self-regulated learning and learning outcomes in speaking skill. Therefore the blended model can be implemented successfully.